Multi-product firms and flexible manufacturing in the global economy - Carsten Eckel; J. Peter Neary (University College Dublin, UCD School of Economics, 2006)
We present a new model of multi-product firms (MPFs) and flexible manufacturing and explore its implications in partial and general equilibrium. International trade integration aects the scale and scope of MPFs through a competition eect and a demand eect. We demonstrate how MPFs adjust in the presence of single-product rms and in heterogeneous industries. Our results are in line with recent empirical evidence and suggest that MPFs in conjunction with flexible manufacturing play an important role in the impact of international trade on product diversity.
hdl:10197/1793
Keywords: F12; L13; 330; Multi-Product Firms; Flexible Manufacturing; General Oligoplistic Equilibrium (GOLE); International Trade; Product Diversity; Außenwirtschaft; Export; Produktionsprogramm; Diversifikation; Anpassungskosten; Partielles Gleichgewicht; Wirtschaftsmodell